2013
DOI: 10.2298/avb1304429k
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and intensity of infection with gastrointestinal nematodes in sheep in eastern Serbia

Abstract: A coprological examination of 680 grazing sheep was performed in Eastern Serbia from March 2011 to November 2012 in order to determine the presence of gastrointestinal (GI) nematode parasites. Fecal samples were randomly collected and examined by using qualitative and quantitative coprological techniques. It was found that 74.56% sheep were infected. Samples that contained nematode eggs were processed for larval development and eleven nematode genera were identified: Haemonchus (46.91%), Ostertagia (25.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Age was considered an important risk factor in GI nematodes (Raza et al, 2007). The present result was in agreement with (Hassan et al, 2011) in Chittagong, Bangladesh and(Kulisic et al, 2013) in Eastern Serbia reported high prevalence rate in adults as compared to young sheep. The possible explanation is that this could be the result of longer exposition of adult sheep to the parasite eggs and larvae during several grazing seasons.…”
Section: Prevalence Of Major Gastrointestinal Nematode In Different Psupporting
confidence: 93%
“…Age was considered an important risk factor in GI nematodes (Raza et al, 2007). The present result was in agreement with (Hassan et al, 2011) in Chittagong, Bangladesh and(Kulisic et al, 2013) in Eastern Serbia reported high prevalence rate in adults as compared to young sheep. The possible explanation is that this could be the result of longer exposition of adult sheep to the parasite eggs and larvae during several grazing seasons.…”
Section: Prevalence Of Major Gastrointestinal Nematode In Different Psupporting
confidence: 93%
“…It was also observed that eggs of GIN in the genera of Heamonchus were the most encountered (80) accounting for 40% prevalence (Table 1). Our results of high prevalence are similar to those of Kulišić et al (2013) and Mphahlele et al (2021) and gastrointestinal parasite infection has a direct effect on the health and productivity of animals, thereby causing a reduction in output and, consequently, a decrease in the owner's and community's income (Mathewoset al, 2022). The predominance of Haemonchus over other GIT parasites has also been reported by Tariq et al (2008) and Wani et al (2011) in Kashmir Valley.…”
Section: Prevalence Of Parasitesupporting
confidence: 79%
“…Fecal examination of sheep revealed that the overall prevalence rate of GIT parasites was 92.6%. In comparison, coprological surveys with similar design conducted in Turkey [21], Spain [22], Bulgaria [23], Republic of Moldova [24], Kenya [25], Brazil [26], Ethiopia [20], Serbia [27], Papua New Guinea [28], India [29], Serbia [30], Nigeria [31], Colombia [17], and Pakistan [32] the prevalence of GIT parasites was 100%, 100%, 98.5%, 94%, 80%, 76.6%, 75.3%, 74.5%, 72%, 68.7%, 64.1% 63.2%, 63.0%, and 53.3%, respectively. In Romania, the study conducted by Indre et al [33] in several flocks from the western part of the country highlighted an overall GIT parasites prevalence value of 75%, but in this study the investigations were focused only on the survey of the occurrence of GIT nematodes and trematodes.…”
Section: Discussionmentioning
confidence: 99%